Perceptions of democracy and the rise of Donald Trump: A framing analysis of Saudi Arabian media. (August 2019) - Isakhan, Benjamin; Nwokora, Zim; Pan, Chengxin
The 2016 US presidential election, which brought Donald J. Trump to power, raised concerns that his ascendency could undermine US democracy promotion and enable illiberal regimes to resist calls for reform. This article seeks to hold this argument up to empirical scrutiny via a framing analysis of coverage of the US election in the Kingdom of Saudi Arabia (KSA). To some extent, the analysis supports the claim: throughout the election, the KSA media offered several substantive criticisms of democracy. However, Trump's campaign also served as a catalyst for a discussion about the merits of democracy, revealing some admiration for its key principles, and an acknowledgement of the challenges it faces in the 21st century.